REGULARITIES OF ELECTROMAGNETIC PROCESSES OF A CONTACTLESS EXCITATION SYSTEM OF AN ASYNCHRONIZED GENERATOR BASED ON A CASCADE THREE-PHASE-THREE-PHASE VOLTAGE MODULATOR IN A SINGLE-STAR CIRCUIT - K. M. Vasyliv (National Technical University "Kharkiv Polytechnic Institute", 2018)
The regularities of electromagnetic processes occurring in a noncontact excitation system of an asynchronized generator based on a cascade three-phase – three-phase voltage modulator in a single-star circuit for the possibility of expanding the range of a two-zone slip of a generator are established. A method for correcting the parameters of the machines’ rotors of modulator and generator is proposed which makes it possible to stabilize the operation of the switch for the slip range from minus one to plus five tenths with maintaining the performance of the asynchronized generator.